The significance of reworked palynomorphs (middle Cambrian to Tournaisian) in the Visean Toca da Moura Complex (South Portugal). Implications for the geodynamic evolution of Ossa Morena Zone - Lopes, Gilda (2014)
Available online 15 August 2013